UniKiosk - Mohsin, Alya Amirah; Arifin, Nur Farzana; Shaharuddin, Adiba Nur Amirah; Abdul Halim, Dhiya Anisah; Shaiful Adzhar, Syahira; Bakri, Hurun Ain Zahrah; Idris, Sufy Rabea Adawiya (Universiti Teknologi MARA, Kedah, 2019)
UniKiosk is a high technology touchscreen device displayed in the library that enables users to seamlessly navigate a range of relevant content without interference from surrounding light or environmental conditions. The integrated, powerful operating system offers users exciting capabilities to deliver rich, engaging content with minimal operational burden required. Beyond a potential for promotion and engagement, hassle-free visual display upgrade. The kiosk features an interactive Wayfinder, online catalog, current awareness service (CAS), live book feeds, student card scanner, event calendar and many more. Therefore, with this interactive kiosk it will attract the users as well as assisting library users to ease the access to information. This interactive kiosk also will further humanize the library community in delivering services and programs that meet the needs for information in a changing and increasingly complex society.